Tomato ACS4 is necessary for timely start of and progression through the climacteric phase of fruit ripening - Hoogstrate, Suzanne W.; van Bussel, Lambertus J. A.; Cristescu, Simona M.; Cator, Eric; Mariani, Celestina; Vriezen, Wim H.; Rieu, Ivo (Frontiers in Plant Science, 2014)
Climacteric fruit ripening, as it occurs in many fruit crops, depends on a rapid, autocatalytic increase in ethylene production. This agriculturally important process has been studied extensively, with tomato simultaneously acting both as a model species and target crop for modification. In tomato, the ethylene biosynthetic genes ACC SYNTHASE2 (ACS2) and ACS4 are highly expressed during fruit ripening, with a combined loss of both ACS2 and ACS4 activity preventing generation of the ethylene burst necessary for fruit ripening. However, the individual roles and importance of ACS2 and ACS4 have not been determined. In this study, we examined specifically the role of ACS4 by comparing the phenotype of an acs4 mutant firstly with that of the wild-type, and secondly with two novel ripening-inhibitor (rin) mutants. Ethylene production during ripening was significantly reduced in both acs4-1, and rin lines, with rin genotypes showing the weaker ethylene burst. Also i) the time between anthesis and the start of fruit ripening and ii) the time required to progress through ripening were significantly longer in acs4-1 than in the wild type, but shorter than in the strongest rin mutant. The delay in ripening was reflected in the lower expression of ripening-related transcripts during the mature green and light red ripening stages. Furthermore, expression of ACS2 and ACS4 was strongly dependent on a functional RIN gene, while ACS2 expression was largely independent of ACS4. Altogether, we show that ACS4 is necessary for normal progression of tomato fruit ripening and that mutation of this gene may provide a useful means for altering ripening traits.